Simultaneous Determination of Prasugrel and Aspirin by Second Order and Ratio First Order Derivative Ultraviolet Spectrophotometry - Shahabuddin N. Alvi; Mehul N. Patel; Prakash B. Kathiriya; Bhavna A. Patel; Shraddha J. Parmar (Journal of Spectroscopy)
Two simple, accurate, and precise UV derivative spectrophotometric methods for the simultaneous determination of Prasugrel and Aspirin in synthetic mixture form have been developed. The first method involves measurement of second order derivative spectra of Prasugrel and Aspirin. The zero crossing wavelengths 267.62 nm and 252.40 nm were selected for estimation of Prasugrel and Aspirin, respectively. In the second method, the first order derivatives of ratio spectra were calculated and used for the determination of Prasugrel and Aspirin by measuring the peak intensity at 268 nm and 290 nm, respectively. The methods were validated as per the ICH guideline Q2 (R1). Beer’s law is followed in the range of 5–45 μg/mL for Prasugrel and 25–150 μg/mL for Aspirin by second order derivative method and 6–22 μg/mL for Prasugrel and 45–165 μg/mL for Aspirin by ratio first order derivative method. The recovery studies confirmed the accuracy of the methods. Relative standard deviations for repeatability and inter- and intraday assays were less than 2%. Hence, the described derivative spectrophotometric methods are simple, accurate, precise, and excellent alternatives to sophisticated chromatographic techniques and can be potentially used for the simultaneous determination of Prasugrel and Aspirin in combined dosage form.